2016
DOI: 10.1002/sca.21295
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the different finishing and polishing procedures on the surface roughness of three different posterior composite resins

Abstract: Finishing and polishing techniques have great importance on the long term success and aesthetics of the composite restorations. In this study it was aimed to examine the effect of three different posterior composites on surface texture with various finishing and polishing procedures. Three different posterior composites, Filtek P60, Clearfil Majesty Posterior and Cavex Quadent Posterior Dense, and three different finishing and polishing procedures diamond finishing burs, tungsten carbide burs and Sof-Lex discs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 20 publications
2
15
0
1
Order By: Relevance
“…Previous studies described the Sof-Lex system as providing a smooth surface when a rougher starting surface was evaluated (ie, silicon paper files, diamond or carbide burs). 7,11,[22][23][24][25] In this study, the control was smoother than the last polishing disc, which may have increased the S a . 26 In contrast to Sof-Lex, the Astropol system polishes the surface with a sequence of three silicon carbide-coated discs, 2,11 which are less abrasive (from 45 to 0.3 μm) and have fewer steps than Sof-Lex.…”
Section: Clinical Studies Havementioning
confidence: 70%
“…Previous studies described the Sof-Lex system as providing a smooth surface when a rougher starting surface was evaluated (ie, silicon paper files, diamond or carbide burs). 7,11,[22][23][24][25] In this study, the control was smoother than the last polishing disc, which may have increased the S a . 26 In contrast to Sof-Lex, the Astropol system polishes the surface with a sequence of three silicon carbide-coated discs, 2,11 which are less abrasive (from 45 to 0.3 μm) and have fewer steps than Sof-Lex.…”
Section: Clinical Studies Havementioning
confidence: 70%
“…Regarding surface morphology, SEM and AFM images showed rough surfaces after the finishing and polishing with Sof-Lex discs. According to Sahbaz et al, 37 the use of Sof-Lex discs results in good finishing and polishing levels compared to other systems. Thus, the irregularities presented by most of the resins in this study may have been due to the displacement of load particles, which produced surface grooves when combined with the use of a rotary instrument.…”
Section: Discussionmentioning
confidence: 99%
“…These data are in conflict with several studies which reported that there were no differences in plaque accumulation throughout the roughness (Ra) range of 0.7 − 1.4 μ m [ 16 , 21 ]. Roughness comparative studies of novel composite materials, nanofills, suprananofills, nanohybrid, and microhybrid after one and multistep finishing and polishing procedures, do not clearly determine which material and polishing system brings the best results [ 2 10 , 14 , 22 ]. However, they confirm that roughness of composite structure depends on both the polishing system used and composite material structure and composition [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%